2019
DOI: 10.1088/1742-6596/1358/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase from the brain of Monopterus albus as detection of metal ions

Abstract: Overwhelming amount of heavy metals discharged due to industrialization is a serious global concern. Thus, an investigation was done on acetylcholinesterase (AChE) from Asian swamp eel, Monopterus albus, as an alternative biosensor to detect various metal ions. AChE from the brain of M. albus was purified through ammonium sulphate precipitation and procainamide affinity chromatography. Enzyme recovery was obtained at 38.73% with the specific activity of 1847 U μg−1. The Michaelis constant (Km) value and maxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
3
0
1
Order By: Relevance
“…To further discuss, in the study done by Sabullah et al, (2014) on P. javanicus liver tissue, ChE was found to be specific towards BTC with (V max /K m ) higher than ATC and PTC. However, a study on M. albus brain tissue by Khalidi et al (2019) found that ATC had the highest (V max /K m ), similar to the result obtained in this study. These results proved that different parts of organs and different species of fish incorporated ChE with different substrate specificity of either ATC, BTC or PTC.…”
Section: Substrate Specificity Profilingsupporting
confidence: 90%
“…To further discuss, in the study done by Sabullah et al, (2014) on P. javanicus liver tissue, ChE was found to be specific towards BTC with (V max /K m ) higher than ATC and PTC. However, a study on M. albus brain tissue by Khalidi et al (2019) found that ATC had the highest (V max /K m ), similar to the result obtained in this study. These results proved that different parts of organs and different species of fish incorporated ChE with different substrate specificity of either ATC, BTC or PTC.…”
Section: Substrate Specificity Profilingsupporting
confidence: 90%
“…Elman reagent known as 5,5'-dithio-bis-2nitrobenzoic acid or DTNB was used as a chromogen to indicates the level of cholinesterase activity. Acetylthiocholine iodide; ATC, was selected as a preferred synthetic substrate due to the highest ratio of the effective coefficient, which was recorded in a previous study [10]. Both chromogen and substrate are Sigma-Aldrich brands.…”
Section: Chemicalsmentioning
confidence: 99%
“…The brain was homogenised in phosphate buffer (0.1 M, pH 7.5) with the ratio of 1:5 (weight of brain: volume of buffer) followed by 10 minutes centrifugation at the 10,000xg in refrigerated condition. Protein precipitation and affinity purification were conducted based on the method previously developed by Khalidi et al [17] using ammonium sulfate concentrations ranging from 20 to 70% of salt. The pellet was solubilised (1:4 weight per volume of extraction buffer) and overnight desaltation.…”
Section: Specimen Preparation and Ache Purificationmentioning
confidence: 99%